Peningkatan Hasil Belajar Siswa Melalui Penggunaan Metode Demonstrasi Berbantuan Canva Pada Pembelajaran Fikih Di Kelas IX A MTS As’adiyah Uloe - Syafi'i, Ahmad; Almutawakkil Alallah; Darnaningsih; Muhammad Ramli (Al-Riwayah : Jurnal Kependidikan, 2025)
This study aims to improve student learning outcomes through the use of demonstration methods assisted by Canva in learning Jurisprudence on the material of Corpse Management in class IX A MTs As'adiyah Uloe. This research is included in class action research. The data collection techniques used were observation, learning outcomes tests, interviews, and documentation. The instruments are observation sheets, learning outcomes tests, and interview sheets. The data collected will be analyzed descriptively qualitative and quantitative. Learning outcomes were analyzed using the KKM which is 78. The subjects of this study were class IX A students totaling 30 people. The research lasted for two months starting from February to March 2025. The results showed that the action in cycle I showed that as many as 23 students were declared complete with a percentage of 77%. The action in cycle II showed that as many as 30 people obtained learning outcomes above KKM 78 with a percentage of 100%. So, the use of the demonstration method assisted by Canva in learning Jurisprudence in class IX A MTs As'adiyah Uloe is able to improve student learning outcomes.